The world of children : foreign cultures in nineteenth-century German education and entertainment - Lässig, Simone, 1964- (Studies in German history ;, 2020)
"In an era of rapidly increasing technological advances and international exchange, how did young people come to understand the world beyond their doorsteps? Focusing on Germany through the lens of the history of knowledge, this collection explores various media for children-from textbooks, adventure stories, and other literature to board games, museums, and cultural events-to probe what they aimed to teach young people about different cultures and world regions. These multifaceted contributions from specialists in historical, literary, and cultural studies delve into the ways that children absorbed, combined, and adapted notions of the world"--